(untitled) (Shahroud Journal of Medical Sciences, 2019)
Background: Swimming pool and similar aquatic environments are polluted bythe chemical and biological compounds produced in swimmers’ body including urine, sweat, saliva, body cells, body dust, respiratory and gastrointestinal tract microorganisms.The aim of study was to investigate the concentration of chemical contaminants in Shahroud swimming pools.Methods:This is a descriptive and cross-sectional study which was held in summer 2016 in6 active Swimming pools of Shahroud. In this study, the arameters of Paraben, Triclosan andHydroquinone were measured in the laboratory. Water sampling was carried out every 10 days when most swimmers were in the pool.Cosmetics was measuredby a high-performance liquid chromatography apparatus equipped with a detector. The results were entered intoSPSS(15) software for analysis.Results: In this study 6 Swimming pools were studied.Our study proved the existence of cosmetic compounds like hydroquinone, PropylParaben and Triclosan with maximum average in part per billion(ppb), For instance between swimming pools used by ladies, their related amounts were respectively listed as 243, 1672.11and 200.8ppb, whereasabout Jacuzzithese digits were differed as 616.33, 1625.88and 57.92ppb.Conclusions: It is the first time that such a research has been done to amount the existence of cosmetic compound in between swimming pools from different areas of Iran and based on this study we showed that swimming pools of high rank of health standard have a better state.